Mapping the global research landscape and trends of older people living alone: a bibliometric analysis - Wu, Yu-Dan; Dong, Jia-Xin; Yu, Fu-Min; Dong, Zhe-Hao; Ma, Wei; Cai, Yue; Cai, Yu-Qing; Mu, Yang; Cui, Xiang; Wang, Yi-Ran; Li, Hui-Jun; Yang, Xiao-Tao; et al. (Frontiers in Aging, 2025)
BackgroundThe global aging trend is becoming increasingly severe, leading to a rise in the number of older adults living alone. As research on this population grows, a comprehensive analysis is essential.ObjectiveThis study examines the current state of research on older adults living alone, identifies key trends and emerging topics, and provides a foundation for future investigations.MethodologyWe conducted a subject search in the Web of Science (WOS) Core Collection database, retrieving articles related to older adults living alone based on titles, abstracts, and keywords from 1965 to 2024. Using CiteSpace (version 6.4.R1 Advanced), we generated collaborative networks among countries and authors, revealing research hotspots and frontiers in this field.ResultsThe study identified 740 relevant articles, showing an overall upward trend in publications. South Korea and China emerged as major contributors, though research remains decentralized. A total of 1,136 cited authors contributed to this field. Recent advances include the application of spatial recognition technology and artificial intelligence to prevent hazardous events among older adults living alone, highlighting a shift toward personalized and intelligent care solutions.ConclusionThis study demonstrates that older adults living alone represent an emerging focus in nursing research, yet international collaboration remains limited. The integration of intelligent devices and technologies to address caregiving challenges has become a prominent research hotspot in recent years.